PENGARUH WORK DEMAND DAN WORK HOME INTERFERENCE TERHADAP BURNOUT PADA PERAWAT WANITA RS. JASA KARTINI - Hekayanti, Kris; Yulianti, Praptini (2021)
This study aims to assess and evaluate the important role of hospital organization in nursing respondents. Nurses are professional workers who play an important role in hospital organizations and are directly related to human services in creating services, attention, assistance, assistance, and support for patients effectively and efficiently. The purpose of this study was to determine the direct effect of work demand on burnout and the indirect effect of work demand on burnout through mediation, namely work home interference on female nurses with dual roles at the Covid-19 Patient Referral Hospital, Jasa Kartini Hospital, Tasikmalaya. This study used a sample of 120 respondents of Dual Role Nurses at the Covid-19 Patient Referral Hospital by using quantitative research types and questionnaire methods. This study uses data analysis techniques with the method of Structural Equation Modeling (SEM) analysis methodologically with AMOSGraphich. In this study, it was obtained from the distribution of online questionnaires to dual-role nurses at the Covid-19 Patient Referral Hospital, Jasa Kartini Hospital, Tasikmalaya. The results show that work demand has a positive and significant effect on burnout directly and indirectly through work home interference mediation.